Improving the Management of Parthenium hysterophorus to Enhance Okra Production through the Application of Chemicals, Adjuvants and Plant Extract Blends in Pakistan - Muhammad Adnan; Muhammad Sikander Hayyat; Qaisar Mumtaz; Muhammad Ehsan Safdar; Fazal ur Rehman; Haroon Ilahi; Koko Tampubolon (Caraka Tani: Journal of Sustainable Agriculture, 2021)
Vegetables are consequently experiencing great yield losses due to weed infestation. Weed management is extremely important for sustainable crop production in all cropping systems. This review paper aimed to provide general information and alternative recommendations for the management of Parthenium hysterophorus weed by chemicals, adjuvants and plant extracts in okra. Different strategies have been used to control parthenium, but no single management solution is sufficient to handle parthenium; hence, different management options need to be combined. Only an integrated approach will achieve effective control over this weed. In areas where parthenium natural enemies are absent, chemical control is an important method of managing this weed. In the control of this plant, the use of chemical herbicides such as chlorimuron ethyl, glyphosate, atrazine, ametryn, bromoxynil and metsulfuron are considered to be efficient. Moreover, various plants have allelopathic potential and attempts have been made to use them in parthenium control. Three allelopathic grasses, namely, Achyranthes aspera, Syzygium cumini and Acacia nilotica are able to minimize the plant growth and inhibit early seedling growth of exotic weed P. hysterophorus. The results recommend that the control of parthenium in okra and other summer vegetables using chemical herbicides with single and combination mode of action is still effective compared to the use of plant extracts. The use of herbicides by adding adjuvants has the potential to minimize the use of excessive herbicides.